ministerial decree no 272/2013 amending certain provisions of the executive regulations of the building law - Egypt (2025)
Ministry of Housing and Urban Communities Ministerial decree no. 272 of the year 2013 قرارت وزارة الإسكان المجتمعات العمرانية قرار وزارى رقم 272 لسنة 2013